Recent Advances in the Discovery and Preclinical Testing of Novel Compounds for the Prevention and/or Treatment of Alcohol Use Disorders. (4th June 2012) - Davies, Daryl L.; Bortolato, Marco; Finn, Deborah A.; Ramaker, Marcia J.; Barak, Segev; Ron, Dorit; Liang, Jing; Olsen, Richard W.
Abstract : Abstract: Alcohol abuse and dependence have a staggering socioeconomic impact, yet current therapeutic strategies are largely inadequate to treat these disorders. Thus, the development of new strategies that can effectively prevent alcohol use disorders (AUDs) is of paramount importance. Currently approved medications attempt to deter alcohol intake by blocking ethanol metabolism or by targeting the neurochemical systems downstream of the cascades leading to craving and dependence. Unfortunately, these medications have provided only limited success as indicated by the continued high rates of alcohol abuse and alcoholism. The lack of currently available effective treatment strategies is highlighted by the urgent call by the NIAAA to find new and paradigm‐changing therapeutics to either prevent or treat alcohol‐related problems. This mini‐review highlights recent findings from 4 laboratories with a focus on compounds that have the potential to be novel therapeutic agents that can be developed for the prevention and/or treatment of AUDs.